Serial Excision of a Nevus Sebaceous of Jadassohn on the Scalp - Sugiatno, Belladikna Brillianty; Widiatmoko, Arif; Dani, Adinda Amalia; Retnani, Diah Prabawati (UI Scholars Hub, 2025)
Background: Nevus sebaceous of Jadassohn (NSJ) is a non-hereditary hamartoma of the skin’s adnexal structures. The incidence of NSJ in newborns is estimated at 0.1-0.3% with no gender or ethnic propensity. Surgical excision is a common treatment for NSJ, although there is no definite consensus on the timing or recommendations for the removal. This article aims to present the advantages of serial excision therapy in a case of NSJ. Case Illustration: A 14-year-old male presented with a complaint of a bump on the scalp since birth, which had progressively enlarged during puberty. Dermatological examination revealed a well-demarcated, yellow-orange verrucous plaque with irregular borders measuring 3x3.5 cm. The diagnosis was confirmed through dermoscopy and histopathology. The patient underwent a three-stage serial excision at 3-4-week intervals. Discussion: The excision technique for NSJ excision was selected based on the location and size of the lesion. Serial excision is a widely used and straightforward method. This method was chosen due to the lesion’s large area. However, NSJ excision on the scalp presents its own challenges due to limited soft tissue flexibility, hair-bearing skin, and a convex surface, which may affect reconstruction outcomes. Conclusion: The three-stage serial excision resulted in complete removal of the NSJ, minimal scarring without significant alopecia, and no recurrence during the 6-month follow-up.